Respuesta :

Answer:

In standard form, the answer is =

[tex](x - 4 {)}^{2} + (y + 2 {)}^{2} = 9[/tex]

Answer:

Step-by-step explanation:

Standard form is

(x - h)^2 + (y - k)² = r²

(h, k) is the center

r is the radius

-----------------------------

x² + y² - 8x + 4y = -11

Regroup

(x² - 8x) + (y² + 4y) = -11

Complete the square for x

(x - 4)² + (y² + 4y) = -11 + (-4)²

Complete the square for y

(x - 4)² + (y + 2)² = -11 + (-4)² + 2²

Simplify

(x - 4)² + (y + 2)² = 9

Instandard form

(x - 4)² + (y + 2)² = 3²

ACCESS MORE